Allergic Rhinitis: What Do We Know About Allergen-Specific Immunotherapy? - Boonpiyathad, Tadech; Lao-Araya, Mongkol; Chiewchalermsri, Chirawat; Sangkanjanavanich, Sasipa; Morita, Hideaki (Frontiers in Allergy, 2021)
Allergic rhinitis (AR) is an IgE-mediated disease that is characterized by Th2 joint inflammation. Allergen-specific immunotherapy (AIT) is indicated for AR when symptoms remain uncontrolled in spite of medication and allergen avoidance. AIT is considered to have been effective if it alleviated allergic symptoms, decreased medication use, improved the quality of life even after treatment cessation, and prevented the progression of AR to asthma and the onset of new sensitization. AIT can be administered subcutaneously or sublingually, and novel routes are still being developed, such as intra-lymphatically and epicutaneously. AIT aims at inducing allergen tolerance through modification of innate and adaptive immunologic responses. The main mechanism of AIT is control of type 2 inflammatory cells through induction of various functional regulatory cells such as regulatory T cells (Tregs), follicular T cells (Tfr), B cells (Bregs), dendritic cells (DCregs), innate lymphoid cells (IL-10+ ILCs) and natural killer cells (NKregs). However, AIT has a number of disadvantages: the long treatment period required to achieve greater efficacy, high cost, systemic allergic reactions and the absence of a biomarker for predicting treatment responders. Currently, adjunctive therapies, vaccine adjuvants and novel vaccine technologies are being studied to overcome the problems associated with AIT. This review presents an updated overview of AIT, with special focus AR.